Dialogic teaching in a Year 5 classroom during cooperative inquiry-based science - Robyn M. Gillies (International Journal of Educational Research Open, 2023)
Over the last two decades there has been a focus on teaching science using an enquiry approach where students are actively engaged in investigations that capture their interest, encourage them to ask questions, and investigate potential solutions to the problems they are confronting. The purpose of this case-study was to investigate how one Year 5 science teacher introduced his students to a unit of science on Matter, used different discourses to capture students’ interest in the enquiry-based tasks, and provided hands-on activities to enable them to test-out their ideas and develop explanations for what they found. The case-study highlights how the teacher used a range of authoritative and dialogic interactions to not only capture students’ interest in the tasks but also to encourage and challenge them to share their ideas with others. It was interesting to note how the students became more adept at expressing their opinions and providing explanations and justifications for the ‘scientific’ understandings they had developed during their enquiry-based science lessons.